Eficiencia energética del sistema de iluminación en la fábrica de cartón, Yaron, para determinar un sistema de iluminación alternativo con paneles fotovoltaicos. - Silvana Elizabeth, Quinatoa Chicaiza (2020)
This project is taking place in the Yaron cardboard factory, located in the province of Tungurahua, Canton Ambato, where problems related to the design and distribution of the lighting system can be evidenced, thus causing the existence of dark areas and high amounts of consumption of energy, generated by the poor selection of luminaires, the same ones that are not appropriate for this type of industrial shed. Taking into account all these antecedents, the project aims to design an alternative lighting system that provides benefits such as: economic and energy savings, safety and efficiency when carrying out production processes within the factory, due to this fact, it is desired to power the system by the use of renewable energy, through photovoltaic panels during the day and connection to the electricity grid during working hours at night and on occasions when the factory deems it necessary. For the design of the alternative lighting system, features such as: design in technical software, number of luminaires to be installed, total power, amount of radiation that exist in the installation area and sizing of the different components that make up the system are being taken into account. Through the designs carried out, an alternative system with photovoltaic panels is achieved that provides uniform lighting, optimal luminance, absence of dazzling glare, adequate contrast conditions, correct colors and above all generates visual comfort for those who work inside the factory, through a viable recovery rate.